Neurological and endocrinological manifestations of 49 children with intracranial pure germinoma at initial diagnosis in Taiwan - Hsin-Yuan Chang; Chiao-Fan Chiu; Shih-Ming Jung; Alex Mun-Ching Wong; Chieh-Tsai Wu; Fu-Sung Lo (Elsevier, 2021)
Background: Intracranial pure germinoma is a rare extragonadal neoplasm. Affected patients may have motor impairment, visual disturbance, neurological signs, and endocrine disorder, depending on the size and location of the tumor. This study investigated and analyzed patients' demographic data and neuroimaging, clinical, laboratory, and endocrinological findings. Methods: We performed a retrospective chart review of 49 children diagnosed with pure germinoma in Taiwan from 1990 to 2018. The initial clinical presentation, tumor markers (beta-hCG, alpha fetoprotein, and carcinoembryonic antigen), pituitary function, and brain images were reviewed and analyzed. Results: This study included 49 patients (37 boys and 12 girls). Their ages ranged from 7.5 to 17.9 years, and the mean age at diagnosis was 13.6 years. Initial symptoms included visual disturbance (n = 23, 47.9%), motor impairment (n = 20, 40.8%), polyuria (n = 20, 40.8%), headache (n = 17, 34.7%), dizziness or vertigo (n = 14, 28.6%), nausea/vomiting (n = 13, 26.5%), and short stature (n = 8, 18.2%). Laboratory data indicated growth hormone deficiency or low IGF-1 levels (n = 18, 85.7%), adrenal insufficiency (n = 21, 77.8%), central diabetes insipidus (n = 27, 55.1%), central hypothyroidism (n = 15, 48.4%), and hypogonadotropic hypogonadism (n = 4, 44.4%). Conclusion: Intracranial pure germinomas may initially manifest as neurological symptoms or endocrinological findings at diagnosis. As endocrinologic presentation is related to delayed diagnosis, clinicians should be aware of patients with such complaints. Laboratory data should be surveyed carefully, and neuroimaging must be considered if the result is abnormal.